Testing asymmetries in Central Bank preferences in a small open economy: A study for Brazil - Edilean Kleber da Silva Bejarano Aragón; Gabriela Bezerra de Medeiros (EconomiA, 2013)
In this paper, we extend Surico's (2007a) model to an open economy and test if the Brazilian Central Bank's loss function is asymmetric with regard to positive and negative deviations of the output gap and of the inflation rate from its target. Furthermore, we use tests for structural breaks to investigate changes in the conduct of policy and monetary authority's preferences. The results revealed that the Central Bank reacted more strongly to deviations of inflation from the target and the output gap after 2003. With regard to the monetary authority's preferences, estimates indicate only an asymmetric preference over an above-target inflation rate until mid-2003. After this period, the evidence obtained by estimating the reaction function with inflation expectations showed that the Central Bank has been more averse to positive deviations of inflation from its target. – – Neste trabalho, nós estendemos o modelo de Surico (2007a) para uma economia aberta e testamos se a funç\~ao perda do Banco Central brasileiro é assimétrica em relaç\~ao a desvios positivos e negativos do hiato do produto e da inflaç\~ao em relaç\~ao à meta. Além disso, nós utilizamos testes de quebra estrutural para investigar alteraç\~oes na conduç\~ao da política e nas preferências da autoridade monetária. Os resultados revelaram que o Banco Central reagiu mais fortemente a desvios da inflaç\~ao em relaç\~ao à meta e ao hiato do produto após 2003. Em relaç\~ao às preferências da autoridade monetária, as estimativas indicaram, em geral, uma assimetria em favor de uma inflaç\~ao acima da meta até meados de 2003. Após esse período, as evidências obtidas através da estimaç\~ao da funç\~ao de reaç\~ao com expectativas de inflaç\~ao mostraram que o Banco Central tem sido mais avesso a desvios positivos da inflaç\~ao em relaç\~ao à meta.
Keywords: E52; E58; C22; 330; Asymmetric preferences; Open economy; Nonlinear interest rate rules; Structural change; Central Bank of Brazil